Primary Gallbladder Small Lymphocytic Lymphoma as a Rare Postcholecystectomy Finding - Kyriakos Psarras; Nikolaos Symeonidis; Euthymia Vlachaki; Minas Baltatzis; Georgios Papatolios; Efstathios Pavlidis; Christina Mouratidou; Ioannis Venizelos; Theodoros Pavlidis; Athanasios Sakantamis; Christina Nikolaidou (Case Reports in Hematology)
Introduction. Primary lymphoma of the gallbladder is an extremely rare entity with approximately 50 cases reported so far. In many of these cases the presenting symptoms were mimicking symptomatic gallstone disease and the diagnosis was made postoperatively, especially when the preoperative imaging results were far from suspicious for malignant disease. Patients and Methods. We report a case of primary lymphoma of the gallbladder in an 85-year-old man with gallstone disease, who was admitted for elective cholecystectomy 2 months after an episode of acute cholecystitis and pancreatitis. Histological evaluation of the specimen revealed a small lymphocytic lymphoma of the gallbladder. This type of primary gallbladder lymphoma has not been previously reported. Discussion. The most common primary lymphomas of the gallbladder are MALT lymphomas and diffuse large B-cell lymphomas, although a variety of other histological types have been reported. The association of these lesions with chronic inflammation is the most convincing theory for their pathogenesis. For lesions confined to the gallbladder, cholecystectomy is considered to be sufficient, while supplementary chemotherapy significantly improves prognosis in more advanced disease.